2014
DOI: 10.3892/ol.2014.2463
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Survivin gene in SGC7901 cell resistance to cisplatin

Abstract: The aim of the present study was to investigate the mechanism of SGC7901 cell resistance to cisplatin (CDDP). SGC7901/CDDP cells were established by the long-term continuous exposure of SGC7901 cells to CDDP in stepwise concentration increments. The morphologies of the SGC7901/CDDP and SGC7901 cells were observed by microscopy. The expression levels of Survivin mRNA and protein in the SGC7901/CDDP and SGC7901 cells were examined by reverse transcription polymerase chain reaction and western blotting respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Overexpression of it mainly indicates inhibition of apoptosis and cell cycle control (42). One study found that Survivin was a positive biomarker for predicting the sensitivity of paclitaxel treatment in gastric cancer patients by western blotting method, however, overexpression of Survivin was closely related with cisplatin and 5-FU treatment sensitivity in gastric SGC7901 cancer cells, and in nude mice, and knockdown of Survivin expression by shRNA, the cisplatin and 5-FU treatment sensitivity of gastric SGC7901 cancer cells and the nude mice enhanced significantly (13,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of it mainly indicates inhibition of apoptosis and cell cycle control (42). One study found that Survivin was a positive biomarker for predicting the sensitivity of paclitaxel treatment in gastric cancer patients by western blotting method, however, overexpression of Survivin was closely related with cisplatin and 5-FU treatment sensitivity in gastric SGC7901 cancer cells, and in nude mice, and knockdown of Survivin expression by shRNA, the cisplatin and 5-FU treatment sensitivity of gastric SGC7901 cancer cells and the nude mice enhanced significantly (13,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, a large population remains resistant to chemotherapy, this suggests that there is still significant room for improvement of diagnosis and therapy in gastric adenocarcinoma patients (7,8). To our knowledge, it is clear that some patients who are positive of human epidermal growth factor receptor-2 (Her-2), P53 and Survivin will indicate poor prognosis due to chemotherapy resistance (9)(10)(11)(12)(13)(14). Therefore, the relationships between these chemotherapy-related biomarkers and the SUVmax of 18 F-FDG PET/CT are needed, to predict the occurrence of chemotherapy resistance and create personalized therapeutic regimens of gastric adenocarcinoma patients before chemotherapy treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant regulations of the Akt-mTOR-survivin and the p53/Sp1-survivin signaling pathways have widely been shown to promote the survival of cancer cells and the induction of anti-cancer drugs resistance ( Cheung et al, 2009 ; Coumar et al, 2013 ; Dong et al, 2014 ; Sun et al, 2014 ; Han et al, 2015 ; Parvani et al, 2015 ; Kim et al, 2016 ). It is not surprising to see that the HDAC2 up-regulated MCF7-TamC3 cells exhibit increased endogenous expression of survivin as compared to the parental hormone therapy-sensitive MCF7 cells because p53 is a negative transcription regulator of the survivin gene ( Mirza et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reversion of chemo-resistance was observed after STAT3 signaling had been blocked 18, 19 . Survivin also contributes to chemo-resistance in cancer patients, and its transcription was induced by the activation of STAT3 14, 15, 20 . These raised a question about whether the combination of STAT3 inhibitor and chemotherapy would have greater anti-tumor effects in ASCC mouse model.…”
Section: Discussionmentioning
confidence: 99%